Synthesis of Spherical Nanostructured g-Al2O3 Particles using Cetyltrimethylammonium Bromide (CTAB) Reverse Micelle Templating - Didi Prasetyo Benu; Erna Febriyanti; Fry Voni Steky; Damar Rastri Adhika; Viny Veronika Tanuwijaya; Ashari Budi Nugraha; Veinardi Suendo; Rino Rakhmata Mukti (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2019)
We demonstrated the synthesis of spherical nanostructured g-Al2O3 using reverse micelle templating to enhance the surface area and reactant accessibility. Three different surfactants were used in this study: benzalkonium chloride (BZK), sodium dodecyl sulfate (SDS) and cetyltrimethylammonium bromide (CTAB). We obtained spherical nanostructured particles only using CTAB that form a reverse micelle emulsion. The particles have wide size distribution with an average size of 2.54 mm. The spherical particles consist of nanoplate crystallites with size 20-40 nm randomly arranged forming intercrystallite spaces. The crystalline phase of as-synthesized and calcined particles was boehmite and g-Al2O3, respectively as determined by XRD analysis. Here, the preserved particle morphology during boehmite to g-Al2O3 transformation opens a facile route to synthesize g-Al2O3 particles with complex morphology. The specific surface area of synthesized particles is 201 m2/g, which is around five times higher than the conventional g-Al2O3 (Aldrich 544833). Spherical nanostructured g-Al2O3 provides wide potential applications in catalysis due to its high density closed packed structure, large surface area, and high accessibility.